Discovering the best practices of Total Quality Management influencing performance in the Moroccan hospitality industry - Bel Haddioui, Ikram (European Scientific Journal, ESJ, 2025)
The present study explores the link between Total Quality Management and hotel performance with a particular focus on identifying best practices from the European Foundation for Quality Management that can enhance business results in the hospitality sector. A quantitative confirmatory study was conducted using a five-point Likert scale questionnaire distributed to 93 Moroccan hotels, specifically targeting senior managers with expertise in quality management. The collected data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results reveal that Total Quality Management (TQM) serves as a key driver of both financial and customer performance within hotels. Furthermore, strategy and processes emerged as the most influential enablers of enhanced hotel performance, as they guide decision-making and ensure that activities are aligned with organizational objectives. While leadership, people, and resources play a more supportive role, they remain essential for the successful implementation of strategic initiatives. Their contribution is realized through fostering employee motivation, promoting effective teamwork, and optimizing the use of financial and technological resources. This research offers a unique empirical contribution by examining how hotels embrace a key managerial approach to enhance their performance. Additionally, the study focuses on a widely recognized model for business excellence, offering a targeted and in-depth analysis of how specific practices within this framework can impact hotel performance.